Basal ganglia alterations in amyotrophic lateral sclerosis - Castelnovo, Veronica; Canu, Elisa; De Mattei, Filippo; Filippi, Massimo; Agosta, Federica (Frontiers in Neuroscience, 2023)
Amyotrophic lateral sclerosis (ALS) has traditionally been associated with brain damage involving the primary motor cortices and corticospinal tracts. In the recent decades, most of the research studies in ALS have focused on extra-motor and subcortical brain regions. The aim of these studies was to detect additional biomarkers able to support the diagnosis and to predict disease progression. The involvement of the frontal cortices, mainly in ALS cases who develop cognitive and/or behavioral impairment, is amply recognized in the field. A potential involvement of fronto-temporal and fronto-striatal connectivity changes in the disease evolution has also been reported. On this latter regard, there is still a shortage of studies which investigated basal ganglia (BG) alterations and their role in ALS clinical manifestation and progression. The present review aims to provide an overview on the magnetic resonance imaging studies reporting structural and/or functional BG alterations in patients with ALS, to clarify the role of BG damage in the disease clinical evolution and to propose potential future developments in this field.